Nanoscale lipid vesicles functionalized with a nitro-aniline derivative for photoinduced nitric oxide (NO) delivery. Issue 1 (17th December 2019) - Sharma, Nancy; Dhyani, Ajay Kumar; Marepally, Srujan; Jose, D. Amilan
Abstract : Photo-controllable, non-toxic and bio-compatible nano-scale vesicles for the controllable release of nitric oxide (NO) have been reported. Abstract : Nanoscale vesicles functionalized with a nitric oxide (NO) releasing molecule 4-nitro-3-(trifluoromethyl)aniline have been reported. The new NO-nano-vesicular donor material shows an effective photo-release of NO upon irradiation with blue light at 410 nm. The kinetics of NO release has been monitored by using simple spectroscopic techniques such as UV-Vis and fluorescence methods. Colorimetric Griess assay and fluorescence DAF assay have been used for the detection and quantification of NO released from vesicles. This new vesicular nanoscale NO donor has the advantages of facile preparation in water, capable of releasing NO in a pure aqueous medium, photo-controlled NO release, bio-compatibility and capacity to modulate the NO donor loading to achieve an essential amount of NO.